A retrospective study of vector‐borne disease prevalence in dogs with proteinuria: Southeastern United States. (8th January 2020) - Purswell, Emily K.; Lashnits, Erin W.; Breitschwerdt, Edward B.; Vaden, Shelly L.
Abstract: Background: Proteinuria is a risk factor for progressive kidney injury in dogs. Enhanced understanding of potential associations between canine vector‐borne diseases (CVBD) and proteinuria is needed. Objectives: To determine the proportion of evaluated proteinuric dogs exposed to ≥1 CVBD, including Babesia spp., Ehrlichia spp., spotted‐fever group Rickettsia, Bartonella spp., Anaplasma spp., hemotropic Mycoplasma spp., Borrelia burgdorferi, and Dirofilaria immitis, and to determine if demographic or clinicopathologic differences exist between proteinuric dogs exposed to CVBD versus proteinuric dogs with no evidence of CVBD exposure. Animals: Two‐hundred nine proteinuric dogs, concurrently tested for CVBD, which were examined at a single academic veterinary hospital between January 2008 and December 2015. Methods: Retrospective cross‐sectional study. Demographic, clinicopathologic, and CVBD test results were extracted from medical records. A multivariable logistic regression model was used to assess associations between CVBD and selected variables. Results: Based on serology and polymerase chain reaction testing, 34% of proteinuric dogs (72/209) were exposed to ≥1 CVBD. Exposure to Rickettsia spp. (19%), Ehrlichia spp. (12%), and B . burgdorferi (9%) were most common. The CVBD exposure was lower in dogs tested in autumn or spring, higher in intact dogs, and higher in dogs with lower serum albumin and higher serum creatinine concentrations. Conclusions and Clinical Importance: Exposure to CVBD, particularly exposure to Rickettsia spp., Ehrlichia spp., and B . burgdorferi was found in proteinuric dogs from the southeast United States. Additional controlled prospective studies examining a potential causal relationship between CVBD and proteinuria are warranted.